Design and Implementation of Automatic Air Flow Rate Control System. (August 2016) - Akbar, A; Saputra, C; Munir, M M; Khairurrijal,
Abstract: Venturimeter is an apparatus that can be used to measure the air flow rate. In this experiment we designed a venturimeter which equipped with a valve that is used to control the air flow rate. The difference of pressure between the cross sections was measured with the differential pressure sensor GA 100-015WD which can calculate the difference of pressures from 0 to 3737.33 Pa. A 42M048C Z36 stepper motor was used to control the valve. The precision of this motor rotation is about 0.15 °. A Graphical User Interface (GUI) was developed to monitor and set the value of flow rate then an 8-bit microcontroller was used to process the control system In this experiment- the venturimeter has been examined to get the optimal parameter of controller. The results show that the controller can set the stable output air flow rate.